Adolescent Wound-Care Self-Efficacy and Practices After Voluntary Medical Male Circumcision—A Multicountry Assessment. (3rd April 2018) - Mavhu, Webster; Hatzold, Karin; Dam, Kim H; Kaufman, Michelle R; Patel, Eshan U; Van Lith, Lynn M; Kahabuka, Catherine; Marcell, Arik V; Mahlasela, Lusanda; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; Ncube, Getrude; et al.
Abstract: Background: Adolescent boys (aged 10–19 years) constitute the majority of voluntary medical male circumcision (VMMC) clients in sub-Saharan Africa. They are at higher risk of postoperative infections compared to adults. We explored adolescents' wound-care knowledge, self-efficacy, and practices after VMMC to inform strategies for reducing the risks of infectious complications postoperatively. Methods: Quantitative and qualitative data were collected in South Africa, Tanzania, and Zimbabwe between June 2015 to September 2016. A postprocedure survey was conducted approximately 7–10 days after VMMC among male adolescents (n = 1293) who had completed a preprocedure survey; the postprocedure survey assessed knowledge of proper wound care and wound-care self-efficacy. We also conducted in-depth interviews (n = 92) with male adolescents 6–10 weeks after the VMMC procedure to further explore comprehension of providers' wound-care instructions as well as wound-care practices, and we held 24 focus group discussions with randomly selected parents/guardians of the adolescents. Results: Adolescent VMMC clients face multiple challenges with postcircumcision wound care owing to factors such as forgetting, misinterpreting, and disregarding provider instructions. Although younger adolescents stated that parental intervention helped them overcome potential hindrances to wound care, parents and guardians lacked crucial information on wound care because most had not attended counseling sessions. Some older adolescents reported ignoring symptoms of infection and not returning to the clinic for review when an adverse event had occurred. Conclusions: Increased involvement of parents/guardians in wound-care counseling for younger adolescents and in wound-care supervision, alongside the development of age-appropriate materials on wound care, are needed to minimize postoperative complications after VMMC.